Frequency of Middle Mesial Canal in Mandibular Molars: Middle Mesial Canal in Mandibular Molars - Chema, Ahmed Mukhtar; Nasir, Sumaira; Hussain, Munawar; Riaz, Afsheen; Atta, Muhammad Hasnain; Shahid, Amira (Pakistan Journal of Health Sciences, 2024)
Being the most difficult to detect unusual canal in mandibular molars, creating greater anatomical complexity and thereby variability, it is important that careful investigation aids in successful endodontic treatments. Objective: To evaluate the incidence and features of MMC in mandibular molars; to study demographic parameters and dental factors that may have an effect on its detection. Methods: A cross-sectional study was performed at Shahida Islam Medical College (SIMC), Lodhran from September 2023 to March 2024, and contained a total of 148 patients. Data was assessed for the presence of MMC in first, second and third mandibular molars. Two expert dental radiologists evaluated the results of the X-ray films. Results: The prevalence of MMC was 18%, with complete and partial compartments seen in more than half the patients (77%). It was shown that MMCs were most commonly observed in 51-65 age group (21.28%); however, there were non-significant differences based on patient’s age and gender or tooth type and position accompanying OAC site. Conclusions: In present study, MMC was noted in 18% patients. Statistically insignificant demographic or dental predictors for MMC were identified